Pesantren, Islam Moderat, dan Etika Politik dalam Perspektif Pendidikan Islam - Ismail Ismail (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
The existency of pesantren with all its variations is still needed in order to continue the struggle of Indonesian Muslim scholars who have pioneered the pesantren. Pesantren struggle not only in da’wah tarbawiyyah, but also in other fields in the life of nation and state, to da'wah siya>siyyah (political). Pesantrens are generating moderate Muslims that are urgently needed in the development of the nation and the country in the future, and pesantren equip their generation with strong competence and ethics based on Islam. The relationship between pesantren, moderate Islam, and political ethics is clearly visible from an educational perspective. Pesantren with its various educational and teaching models resulted in output generations of moderate Muslims, who uphold ethical values, which will accelerate the nation-wide development process in various sectors. The principal of political ethics in Islam is at least three things: (1) the political orientation of the amar ma’ruf nahi munkar, (2) the ethics of leadership, and (3) the ethics of government management